Ecomorphology of Ostrea edulis (Linnaeus, 1758) in Kuala Gigieng Waters, Aceh Besar District - Chitra Octavina; Fredinan Yulianda; Majariana Krisanti; Isdradjad Setyobudiandi (Masyarakat Moluska Indonesia, 2021)
Ostrea edulis is one of the most common types of meat oysters and is commonly consumed by people in Kuala Gigieng, but until now there is not much scientific information about this species. The purpose of this study was to describe the ecomorphology of Ostrea edulis in Kuala Gigieng waters. This research was conducted from August to September 2013 in Kuala Gigieng Waters, Aceh Besar District. The method used in this research is purposive sampling. Identification of samples based on shell morphological characteristics including the exterior and interior of the shell using a magnifier lamp. The results showed that Ostrea edulis found in Kuala Gigieng waters had round, rough, hard, thick and uneven shells. The two valves are also not the same size, where the left valve is more concave than the right valve which tends to be flat. This is a form of the adaptation pattern of Ostrea edulis in Kuala Gigieng which tends to have a medium sand and clay sand substrate with a fairly high predation from both natural and human predation.